2023
DOI: 10.1021/acsnano.3c03301
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Porosity in Microellipsoids Cloaks Interparticle Capillary Attraction at Fluid Interfaces

Abstract: Anisotropic particles pinned at fluid interfaces tend toward disordered multiparticle configurations due to large, orientationally dependent, capillary forces, which is a significant barrier to exploiting these particles to create functional self-assembled materials. Therefore, current interfacial assembly methods typically focus on isotropic spheres, which have minimal capillary attraction and no dependence on orientation in the plane of the interface. In order to create longrange ordered structures with comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
(202 reference statements)
0
11
0
Order By: Relevance
“…Previous studies in liquid–solid CE have demonstrated that the tribogeneration performance on a flat surface is influenced by their corresponding surface roughness. ,, Therefore, CEC efficiency is also anticipated to be affected by the surface roughness of catalytic nanoparticles, e.g., raspberry-like, patchy, and/or hollow nanoparticles. More remarkably, a recent study showcased that the nanoscale porosity on particle surfaces can effectively prevent undesired particle agglomeration upon ultrasonication , (Figure e). Improving particle dispersity is helpful to expose more surface area for liquid–solid CE.…”
Section: Enhancement Pathway For Cecmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies in liquid–solid CE have demonstrated that the tribogeneration performance on a flat surface is influenced by their corresponding surface roughness. ,, Therefore, CEC efficiency is also anticipated to be affected by the surface roughness of catalytic nanoparticles, e.g., raspberry-like, patchy, and/or hollow nanoparticles. More remarkably, a recent study showcased that the nanoscale porosity on particle surfaces can effectively prevent undesired particle agglomeration upon ultrasonication , (Figure e). Improving particle dispersity is helpful to expose more surface area for liquid–solid CE.…”
Section: Enhancement Pathway For Cecmentioning
confidence: 87%
“…Copyright 2022 Elsevier. (e) Reproduced with permission from ref . Copyright 2023 American Chemical Society.…”
Section: Enhancement Pathway For Cecmentioning
confidence: 99%
“…An earlier study on interfacially trapped hydrophobically modified spherical particles (250 nm) revealed that the predominant interaction influencing the network formation is the capillary interaction arising from the non-uniform pinning of the three-phase contact line [59]. These interactions are usually more prominent as we move away from isotropic particles towards systems containing chemically anisotropic particles (i.e., Janus or patchy particles) [40,[60][61][62][63][64], or shape anisotropic particles [65], as well as the rough silica particles used in this study.…”
Section: Thermodynamic Model Fit To the Measured Surface Pressure Iso...mentioning
confidence: 99%
“…Among various interparticle interactions between colloids at the interface which contribute to collective interfacial microstructure and properties, attractive capillary interactions are significant and originate from curved menisci around the particle 5 . An undulated three-phase contact line has been reported to arise from either particle surface roughness in otherwise smooth spheres 5 or shape anisotropy as in ellipsoids 6 , deforming the fluid interface in a quadrupolar fashion 7,8 . While theoretical predictions of roughness causing local contact line pinning undulations that scale to a quadrupolar deviation in the far field date back to 2000 5,9 , and its impact on emulsions observed shortly thereafter 10 , it was only in 2017 that gel-trapping was used to perform ex situ measurements of the deformation to confirm 11 .…”
Section: Introductionmentioning
confidence: 99%